Spatial frictions - Kristian Behrens; Giordano Mion; Yasusada Murata; Jens Suedekum (Institute for the Study of Labor (IZA), 2013)
The world is replete with spatial frictions. Shipping goods across cities entails trade frictions. Commuting within cities causes urban frictions. How important are these frictions in shaping the spatial economy? We develop and quantify a novel framework to address this question at three different levels: Do spatial frictions matter for the city-size distribution? Do they affect individual city sizes? Do they contribute to the productivity advantage of large cities and the toughness of competition in cities? The short answers are: no; yes; and it depends.
Keywords: F12; R12; 330; trade frictions; urban frictions; city-size distribution; productivity; markups